Veteran masculinities and audiovisual popular music in post-conflict Croatia: a feminist aesthetic approach to the contested everyday peace. (4th May 2019) - Baker, Catherine
ABSTRACT: In Croatia, campaigners for a more critical public reckoning with the memory of Croatia's 'Homeland War' (1991–5) and the national past confront embeddings of hegemonic myths of the war into everyday life. Among these are the stardom of a musician whose 'patriotic' music claims the same moral authority as the Croatian veterans' movement and whose public persona has embodied militarised masculinity since he became a wartime star. Popular music and youth engagement with it is thus among the sites where everyday understandings of peace are being contested. By exploring the audiovisual aesthetics of the song/video through which this musician re-engaged with veterans' activism in 1998, and showing that popular music spectatorship seeps into the everyday micropolitics of young people building and contesting peace, the paper argues that for critical peace and conflict studies to understand the affective politics of post-conflict masculinities, they must combine a feminist and aesthetic consciousness.